IMPLEMENTASI PENDEKATAN DEEP LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Naralisa Fatiha; syafitri umminnisa; cindi tamala; mega yulia nurcholina; Dine Trio Ratnasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This research is motivated by the need for the transformation of social studies learning in grade IV of elementary school which requires the development of critical thinking skills through a contextual and meaningful learning approach. The Merdeka Curriculum emphasizes the importance of implementing learning methods that encourage high-level thinking skills (HOTS) and the formation of Pancasila student profiles. The purpose of this study is to analyze and describe the implementation of the Deep learning approach in social studies learning and assess its contribution to improving students' critical thinking skills. This study uses a qualitative method with a case study approach. Data was obtained through observation, in-depth interviews, and document analysis. The results of the study show that the application of the Deep learning approach is carried out consistently through learning that integrates mindful, meaningful, and joyful learning. The teacher acts as a facilitator who guides students to think reflectively, analytically, and is able to relate concepts to real experiences. This implementation has been proven to improve students' critical thinking skills which is reflected in the ability to put forward logical arguments, evaluate information, and conduct self-reflection. Thus, the Deep learning approach makes social studies learning more active, contextual, and contributes to the development of critical thinking skills that are relevant to the demands of 21st century education.